Minimum wage not yet for everyone: On the compensation of eligible workers before and after the minimum wage reform from the perspective of employees - Patrick Burauel; Marco Caliendo; Alexandra Fedorets; Markus M. Grabka; Carsten Schröder; Jürgen Schupp; Linda Wittbrodt (DIW Economic Bulletin, 2017)
Calculations based on data from the Socio-Economic Panel (SOEP) show that after the introduction of a statutory minimum wage in Germany in January 2015, the wage growth of eligible employees with low wages accelerated significantly. Before the reform, the nominal growth in contractual hourly wages in the lowest decile, the bottom tenth of the pay distribution, was less than two percent in the long-term two-year average, while from 2014 to 2016 it was around 15 percent. Nevertheless, in the first half of 2016, around 1.8 million employees who were eligible for the minimum wage of 8.50 euros gross per hour still earned contractual hourly wages below this level. In 2015, the count was approximately 2.1 million workers, and in the year before the introduction of the minimum wage, almost 2.8 million. The figures for 2015 and 2016 reported here are thus higher than corresponding figures from company surveys. Despite the disproportionate increase in wages in the lowest wage decile, many workers are still not earning the minimum wage. The objectives of the German Minimum Wage Act (Mindestlohngesetz) are often not being met, especially among the marginally employed. Instruments for better enforcement of the Minimum Wage Act include more frequent inspections, stricter sanctioning, more effective grievance procedures for workers, and stricter requirements for the documentation systems (especially timekeeping).
Keywords: B41; C83; D31; J31; 330; minimum wage; inequality; employment; SOEP